Comprehensive Brachytherapy: Physical and Clinical Aspects. Issue 11 (23rd October 2013) - Thomadsen, Bruce
Abstract : Comprehensive Brachytherapy: Physical and Clinical Aspects. Venselaar J., Baltas D., Meigooni A., Hoskin P., Imaging in Medical Diagnosis and Therapy, William R. Hendee, Series Editor. CRC/Taylor & Francis Group, Boca Raton, FL, 2013. Hardback 535 pp. Price: $199.95. ISBN: 9781439844984.